Wear behavior of light-weight and high strength Fe-Mn-Ni-Al matrix self-lubricating steels. Issue 4 (April 2019) - Han, Liuliu; Li, Kun; Qian, Cheng; Qiu, Jingwen; Zhou, Chengshang; Liu, Yong
Abstract: The good combination of mechanical and tribological properties for self-lubricating materials is crucial. In this work, novel self-lubricating Fe-16.4Mn-4.8Ni-9.9Al-xC (wt%) steels containing graphite phase were fabricated using mechanical alloying and spark plasma sintering. The compositions of the steels were designed by using thermodynamic calculation, and the effect of carbon addition on the microstructure was further investigated. The steel possesses high hardness of 621 HV, high yield strength of 1437 MPa and good fracture toughness at room temperature. The yield strengths are still above 600 MPa at 600 °C. The tribological behavior and mechanical properties from room temperature to 800 °C were studied, and the wear mechanisms at elevated temperatures were discussed. The steel has a stable friction coefficient of 0.4 and wear rate in a magnitude of 10 −6 mm 3 /N·m below 600 °C. The good tribological properties of the steels were mainly attributed to the high hardness, lubrication of graphite and stable surface oxide layer.